PUTUSAN ULTRA PETITA MAHKAMAH KONSTITUSI DALAM PERKARA PENGUJIAN KONSTITUSIONALITAS UNDANG-UNDANG - Zendy Wulan Ayu W.P; Haidar Adam (Yuridika, 2014)
This research aimed to analyze the Indonesia constitutional court decisions which contain dissenting opinion regarding the constitutionality of the law. As a part of constitutional court law of procedure, some constitutional judges allowed to give their different opinion against the majority of the judges. In one hand, this action has reflected the independency of the judges cum the independency of the judicial power. On the other hand the dissenting opinion has raised a question concerning the legitimacy of the decision since the decision was not decide unanimously. This research is doctrinal research which means that all the material will be analyzed by using the law, court decisions and law principles.Keywords: dissenting opinion, decision, constitutional review.